Artikel Analisis Perbandingan Zakat Harta Temuan (Rikaz) Dalam Perspektif Hukum Islam dan Hukum Positif di Indonesia: Pendahuluan, Metode Penelitian, Pembahasan, Zakat Harta Temuan (Rikaz) Dalam Perspektif Hukum Islam, Zakat Harta Temuan (Rikaz) Dalam Perspektif Hukum Positif di Indonesia, Kesimpulan, Saran - MUTAQIN, M ZAENUL (Maliki Interdisciplinary Journal, 2025)
This article analyzes the comparison of zakat on found treasure (rikaz) from the perspective of Islamic law and positive law in Indonesia. In Islam, rikaz is defined as ancient buried treasure discovered without a known owner, differing from luqathah (lost and found items). Islamic law mandates zakat on rikaz at a rate of one-fifth (20%) without requiring nisab (minimum amount) or haul (holding period), based on the hadith of Prophet Muhammad (peace be upon him). The remaining 80% belongs to the finder. Regarding its recipients, the majority of scholars (Shafi'i, Maliki, Hanbali) state that it should be distributed to the eight categories of zakat beneficiaries (mustahik), while the Hanafi school views it as belonging to the Baitul Mal (Islamic treasury). On the other hand, Indonesia’s positive law does not explicitly regulate zakat on found treasure. The Civil Code (KUHPerdata) governs the division of discovered treasure between the finder and landowner. If the object is considered cultural heritage, Law No. 11 of 2010 on Cultural Heritage applies, requiring reporting and potentially granting ownership to the state with compensation. Law No. 23 of 2011 on Zakat Management recognizes zakat as a religious obligation, but does not detail rikaz zakat. Under positive law, paying zakat is voluntary. These differences reflect distinct philosophical foundations: Islam emphasizes wealth distribution, while positive law focuses on ownership and cultural preservation. Harmonization of both systems requires education and collaboration among stakeholders.